Implementing the National Service Framework for long-term (neurological) conditions: service user and service provider experiences. (April 2014) - Sixsmith, Judith; Callender, Matthew; Hobbs, Georgina; Corr, Susan; Huber, Jörg W.
Abstract Purpose: This research explored the experiences of service users and providers during the implementation of the National Service Framework (NSF) for Long-Term (Neurological) Conditions (LTNCs). Method: A participatory qualitative research design was employed. Data were collected using 50 semi-structured interviews with service users, 25 of whom were re-interviewed on three occasions. Forty-five semi-structured interviews were also conducted with service providers who worked with individuals with LTNCs. Interviews focused on health, well-being and quality of life in relation to service provision, access and delivery. Data were thematically analysed individually and collaboratively during two data analysis workshops. Results: Three major themes were identified that related to the implementation of the NSF: "Diagnosis and treatment", "Better connected services" and "On-going rehabilitation". Service users reported that effective care was provided when in hospital settings but such treatments often terminated on return to their communities despite on-going need. In hospital and community settings, service providers indicated that they lacked the support and resources to provide continuous care, with patients reaching a crisis point before referral to specialist care. Conclusion: This research highlighted a range of issues concerning the recent UK-drive towards patient-centred approaches within healthcare, as service users were disempowered within the LTNC care pathway. Moreover, service providers indicated that resource constraints limited their ability to provide long-term, intensive and integrated service provision. Implications for Rehabilitation Our research suggests that many service users with long-term neurological conditions experienced disconnections between services within their National Service Framework care pathway. For health and social care practitioners, a lack of continuity within a care pathway was suggested to be most pertinent following immediate care and moving to rehabilitative care. Our findings also indicate that service providers lack the necessary financial resources and staffing capacity to provide on-going and comprehensive rehabilitation. This article aims to help practitioners better understand particular issues during the implementation of the National Service Framework for long-term neurological conditions from the perspectives of service users and service providers.